The cabin in the woods [videorecording (DVD)] - Whedon, Joss, 1964-; Goddard, Drew, 1975-; Hemsworth, Chris; Hutchison, Anna, 1986-; Williams, Jesse, 1981-; Whitford, Bradley (Lions Gate Home Entertainment, 2012)
A rambunctious group of five college friends steal away for a weekend of debauchery in an isolated country cabin, only to be attacked by horrific supernatural creatures in a night of endless terror and bloodshed. As the teens begin to exhibit standard horror movie behavior, a group of technicians in a control room are scrutinizing and sometimes even controlling every move the terrified kids make. Do they have any chance of escape?